2021
DOI: 10.3390/ijms22157968
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-Protector Lipidic Cilastatin Derivatives as Structure-Directing Agents for the Synthesis of Mesoporous Silica Nanoparticles for Drug Delivery

Abstract: Mesoporous silica nanomaterials have emerged as promising vehicles in controlled drug delivery systems due to their ability to selectively transport, protect, and release pharmaceuticals in a controlled and sustained manner. One drawback of these drug delivery systems is their preparation procedure that usually requires several steps including the removal of the structure-directing agent (surfactant) and the later loading of the drug into the porous structure. Herein, we describe the preparation of mesoporous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…A lipidic derivative of L-arginine, N-oleoyl-L-arginine, was first synthesized to act as Drug-Structure-Directing Agent DSDA, i.e., a template with pharmacological activity to drive the formation of MSNs, a concept previously introduced by us [ 34 , 48 , 49 ]. For this purpose, DSDA must have an amphipathic character, hydrophilic headgroup and hydrophobic tail to address the formation of micelles in water.…”
Section: Resultsmentioning
confidence: 99%
“…A lipidic derivative of L-arginine, N-oleoyl-L-arginine, was first synthesized to act as Drug-Structure-Directing Agent DSDA, i.e., a template with pharmacological activity to drive the formation of MSNs, a concept previously introduced by us [ 34 , 48 , 49 ]. For this purpose, DSDA must have an amphipathic character, hydrophilic headgroup and hydrophobic tail to address the formation of micelles in water.…”
Section: Resultsmentioning
confidence: 99%
“…The pore size distribution showed a maximum in a range between 2.2 and 5.1 nm, which revealed a morphology of mesoporous materials. The large hysteresis loop and wide pore size distribution suggest the adsorption of N 2 molecules in the intraparticle voids that corresponds with the internal hollow of these particles [34,48,49]. The low-angle X-ray diffraction pattern of the calcined material showed a XRD peak at 1.6 (2θ), which suggests an ordered distribution of the pores in the nanostructure of the MSNs (Fig.…”
Section: Synthesis and Characterization Of Mesoporous Silica Nanopart...mentioning
confidence: 93%
“…A lipidic derivative of L-arginine, N-oleoyl-L-arginine, was rst synthesized to act as Drug-Structure-Directing Agent DSDA, i.e., a template with pharmacological activity to drive the formation of MSNs, concept previously introduced by us [34,48,49]. For this purpose, the DSDA must have an amphipathic character, hydrophilic headgroup and hydrophobic tail, to address the formation of micelles in water.…”
Section: Synthesis and Characterization Of N-oleoyl-l-argininementioning
confidence: 99%
“…The performance efficacy of the retained structure-directing micelles and their complexes is explored by monitoring the compatibility issues surfactants towards cancer therapy [ 76 ]. Similarly, the newly designed synthetic templates, i.e., drug-structure-directing complexes, have been employed to fabricate MSNs with exceptional functional and structural advantages [ 77 79 ]. Compared to traditional surfactants, these drug-complex templates exhibit higher stability and robustness, resulting in the MSNs with high surface area and pore volume.…”
Section: Types and Fabrication Strategiesmentioning
confidence: 99%
“…Interestingly, the lamellar pillars were grown inside the hollow shells of MSNs. Further, the authors demonstrated the fabrication of MSNs to deliver the lipidic derivatives of cilastatin, a kidney protector [ 79 ]. Similarly, Stewart et al explored the encapsulation of surfactant-like drugs (for instance, octenidine dihydrochloride) to fabricate the drugs structure-directing agents’ concept for antimicrobial therapy [ 77 ].…”
Section: Types and Fabrication Strategiesmentioning
confidence: 99%